Mass transfer simulation of liquid-liquid extraction systems using an educational software (2018)
In order to improve the learning process about the unit operation of Liquid Extraction, it is presented a GUI in Matlab® for designing extracting systems with different types of contact, where the stages reach the equilibrium between both liquid phases. The program called ExtractING is an application of theoretical studies and material balances presented in highly relevant documents and popular academic books, which has a general procedure that initiates by introducing feed and solvent quantities with their respective compositions, and a raffinate exit condition for multistage equipment. It is necessary to introduce the ternary system (solute, dissolvent, diluent) and an operating temperature to calculate equilibrium conditions with Van Laar activity model equations. Material balances, multiple iterative routines, and equilibrium diagrams were used to calculate raffinate and extract conditions in all the stages as well as the minimum number of stages needed for the required separation allowing the user to get the approximate size and cost of the equipment, making this software a powerful academic tool. With the program, it was compared the maximum separation for specified conditions between counter-current and crosscurrent equipment, the separation percentage behavior with an increasing feed quantity, and the separation behavior with variations of temperature.